2018
DOI: 10.1016/j.chemosphere.2018.08.044
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical advanced oxidation processes (EAOPs) as alternative treatment techniques for carwash wastewater reclamation

Abstract: Electrochemical advanced oxidation processes such as electrooxidation (EO), electrooxidation with hydrogen peroxide generation (EO-HO) and electro-Fenton process (EF) have been investigated as alternative treatment techniques for complete removal of anionic surfactants and organic matters from real carwash wastewater. The electrochemical processes were performed with acidified real carwash wastewater using boron doped anode and carbon felt cathode. In all cases, the chemical oxygen demand (COD) removal efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 95 publications
(29 citation statements)
references
References 53 publications
1
28
0
Order By: Relevance
“…[92] The scavenging effect of the Cl À ions prevails at high concentration where it is oxidized to ClO À by the electrogenerated hydroxyl radical [Eq. (9)(10)(11)(12). Subsequently, the produced ClO À can further reacts with hydroxyl radical in several steps to form different RCS according to Eq.…”
Section: Reactive Chlorine Speciesmentioning
confidence: 99%
See 2 more Smart Citations
“…[92] The scavenging effect of the Cl À ions prevails at high concentration where it is oxidized to ClO À by the electrogenerated hydroxyl radical [Eq. (9)(10)(11)(12). Subsequently, the produced ClO À can further reacts with hydroxyl radical in several steps to form different RCS according to Eq.…”
Section: Reactive Chlorine Speciesmentioning
confidence: 99%
“…Brito et al (2015) [53] showed that during anodic polarization at low Cl À concentrations, there was a shift in current/potential curves towards the negative direction, which was more pronounced with higher sp 3 /sp 2 ratio (sp 3 /sp 2 = 329)) BDD compared to low sp 3 /sp 2 ratio BDD (sp 3 /sp 2 ratio = 175), which suggested that Cl 2 gas could be predominantly favored at higher current with high sp 3 /sp 2 ratio BDD. (8)(9)(10)(11) or faster direct Cl À oxidation at the anode to form Cl 2 , which is a precursor for the production of RCS. The formation of these species via the electrochemical reactions are assumed to be responsible for the peak observed in the voltammogram.…”
Section: Reactive Chlorine Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…[2]. Many European coun-tries have legislation for water recycling in car washing stations to reduce the volume of water consumed as well as reduce the pollutant release to the municipal treatment systems [7]. According to the Turkey Statistical Institute [8], the number of total cars is 23 million, but there is no statistical information about water consumption for car washes.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these systems are not sufficient for the quality of reuse water [10]. Some treatment methods used for the treatment of car wash wastewater include physicochemical processes [10][11][12][13], electro/chemical coagulation [2,14,15], chemical oxidation [4], electrochemical AOPs [7] and electrooxidation [16]. Although high efficiency is obtained with membrane processes, such processes require large areas and high costs.…”
Section: Introductionmentioning
confidence: 99%